Genetically engineered CD80–pMHC-harboring extracellular vesicles for antigen-specific CD4+ T-cell engagement - Ishina, Irina A.; Kurbatskaia, Inna N.; Mamedov, Azad E.; Shramova, Elena I.; Deyev, Sergey M.; Nurbaeva, Kamila S.; Rubtsov, Yury P.; Belogurov, Alexey A.; Gabibov, Alexander G.; Zakharova, Maria Y. (Frontiers in Bioengineering and Biotechnology, 2024)
The identification of low-frequency antigen-specific CD4+ T cells is crucial for effective immunomonitoring across various diseases. However, this task still encounters experimental challenges necessitating the implementation of enrichment procedures. While existing antigen-specific expansion technologies predominantly concentrate on the enrichment of CD8+ T cells, advancements in methods targeting CD4+ T cells have been limited. In this study, we report a technique that harnesses antigen-presenting extracellular vesicles (EVs) for stimulation and expansion of antigen-specific CD4+ T cells. EVs are derived from a genetically modified HeLa cell line designed to emulate professional antigen-presenting cells (APCs) by expressing key costimulatory molecules CD80 and specific peptide–MHC-II complexes (pMHCs). Our results demonstrate the beneficial potent stimulatory capacity of EVs in activating both immortalized and isolated human CD4+ T cells from peripheral blood mononuclear cells (PBMCs). Our technique successfully expands low-frequency influenza-specific CD4+ T cells from healthy individuals. In summary, the elaborated methodology represents a streamlined and efficient approach for the detection and expansion of antigen-specific CD4+ T cells, presenting a valuable alternative to existing antigen-specific T-cell expansion protocols.